Risk Factors for Contracting Invasive Meningococcal Disease and Related Mortality: A Systematic Literature Review and Meta-analysis. (June 2022) - Dubey, Himanshu; Oster, Philipp; Fazeli, Mir Sohail; Guedes, Sandra; Serafini, Paul; Leung, Lisa; Amiche, Amine
Highlights: This is the first meta-analysis of risk factors for IMD across all age groups. HIV + status, passive smoke exposure, and crowded living spaces increase risk of IMD. Increased risk for IMD-related mortality was related to age and serogroup. There is a lack of research reporting on interactions between risk factors. Abstract: Objectives: To describe risk factors (RFs) and quantify their effects in invasive meningococcal disease (IMD) and associated mortality across all age groups based on the available published literature. Methods: A systematic literature review (SLR) was conducted via MEDLINE® and Embase. Study selection, data extraction, and quality assessment were performed by two independent reviewers. Associations between RFs and outcomes were quantified via a meta-analysis (MA). Results: Seventy-four studies (date range 1950 – 2018) were included in the SLR. Statistically significant RFs for contracting IMD identified from the SLR (within-study) included previous IMD infection and young age (0 – 4 years). MA indicated that significant RFs for contracting IMD (11 studies) were: HIV-positive status, passive smoke exposure, and crowded living space. In the MA for IMD-related mortality risk (11 studies), age 25 – 45 years (vs. 0 – 5 years) and serogroup C (vs. serogroup B) were significantly associated with increased risk. Conclusions: Previous findings of higher risk for IMD contraction with smoke exposure and crowded living conditions in children/adolescents have been extended by this SLR/MA to all age groups. We provide strong evidence for higher risk of IMD in HIV-positive individuals, and confirm previous findings of higher IMD-related mortality risk in adults aged 25 – 45.